Developing a program to train nurses in exploration and management of pre-operative anxiety and information needs of patients (PEMPAINP) - Sawan Dankyi; Million Bimerew; Jennifer-Anne Chipps (Journal of Perioperative Nursing)
Objective: The objective of the study was to develop a program to train nurses to explore and manage pre-operative anxiety and information needs of patients.